Perda de espécies de formigas em ambientes amazônicos e savânicos no Brasil : perturbações ambientais e gradientes longitudinais - Paiva, Antônio Fernando de (2019)
Assessing biodiversity and the effects of environmental changes is necessary in the current scenario of rapid human changes in the Brazilian Amazon and its neighboring biomes. The purpose of this paper is to understand how ant genera / species react to environmental disturbances along a large geographic gradient. Ant collectors, both in forest areas and Savanna areas, are relatively easy and effective as bioindicators of human disturbances. From studies published in scientific journals and grey literature that have lists of ant species, we created a database of preserved and disturbed environments in the Amazon and in the surrounding savannas: Pantanal, Cerrado and Caatinga. Associated with the lists, we also collected information about the ant collection method, the environmental situation regarding the level of anthropic interference, latitude and longitude of the collection site. In total, 132 papers with lists of ant species divided in the biomes surveyed, totaling 350 collected points were found. Our analyzes showed that the number of species differs between Amazon environments and Savannas environments, and that the disturbances decrease the number of species in both environments, but they act more strongly in the Savannas. There was no effect of the latitude on the number of species, neither of Amazonian environments nor of Savannah environments. The longitude was the best geographic correlate of ant species richness in all environments analyzed, the westernmost regions of the continent present the highest species values. In disturbed environments, in the Amazon and in the Savanas, the number of species is low independent of the longitude. In preserved environments, the number of species decreases with longitude. So that close to the center of the continent, there is a great difference between the number of species of ants of preserved and disturbed environments, this difference falls until being very similar in areas near the coast. Independent of the biome, whatever the environmental filter that causes change in wealth along the geographic axis, it is broken in disturbed environments.